Intensity Modulated Radiotherapy (IMRT) With Carbon Ion Boost in the Multimodal Treatment of Salivary Duct Carcinoma - Adeberg, Sebastian; Windisch, Paul; Ehret, Felix; Baur, Melissa; Akbaba, Sati; Held, Thomas; Bernhardt, Denise; Haefner, Matthias F.; Krauss, Juergen; Kargus, Steffen; Freudlsperger, Christian; Plinkert, Peter; et al. (Frontiers in Oncology, 2019)
(1) Background: To assess outcomes and treatment related toxicity following intensity-modulated radiotherapy (IMRT) and a Carbon Ion Radiotherapy (CIRT) boost for salivary duct carcinoma (SDC). (2) Methods: Twenty-eight consecutive patients with SDC who underwent a postoperative (82%) or definitive (18%) radiation therapy between 2010 and 2017 were assessed in this retrospective single-center analysis. CIRT boost was delivered with median 18 Gy(RBE) in 6 daily fractions, followed by an TomoTherapy®-based IMRT (median 54 Gy in 27 daily fractions). Treatment-related acute toxicity was assessed according to CTCAE Version 4. (3) Results: Tumors were most commonly located in the major salivary glands (n=25; 89%); 23 patients (82%) received previous surgery (R0: 30%; R1: 57%; R2: 4%; RX: 19%). Median follow-up was 30 months. Four patients (14%) patients experienced a local relapse and 3 (11%) developed locoregional recurrence. The two-year local control (LC) and locoregional control (LRC) was 96% and 93%, respectively. Median disease-free survival (DFS) was 27 months, metastasis-free survival (MFS) was 69 months, and overall survival (OS) was 93 months. Acute grade 3 toxicity occurred in 11 patients (mucositis, dermatitis, xerostomia; n=2 each (7%) were the most common) and 2 osteonecrosis of the mandibular (grade 3) occurred. No patients experienced grade ≥4 toxicities. (4) Conclusions: Multimodal therapy approaches with surgery followed by IMRT and CIRT boost for SDC leads to good local and locoregional disease control. However, the frequent occurrence of distant metastases limits the prognosis and requires optimization of adjuvant systemic therapies.